Design of a kilohertz repetition rate, low-emittance S-band photoinjector - He, Tianhui; Shan, Lijun; Wang, Hanbin; Xiao, Dexin; Zhou, Kui; Li, Peng; Wang, Jianxin; Xu, Hanxun; Zhou, Zheng; Li, Ming; Wu, Dai (Frontiers in Physics, 2024)
Low-emittance photoinjector enabled cutting-edge scientific instruments, such as free electron laser, inverse Compton scattering light source and ultrafast electron diffraction, will greatly benefit from improved repetition rate. In this paper, we proposed a specially designed S-band radiofrequency (RF) photoinjector to obtain low emittance and kilohertz (kHz) high repetition rate simultaneously. By lowering gradient, much lower RF power is needed to feed the electron gun and then the heat problem is much easier to handle. Meanwhile, by optimizing the length of the gun's first cell from normal case of 0.6-cell to 0.4-cell, the launch phase as well as the extraction field is significantly improved, thus ensuring generation of low emittance electron beams. In our design, the proposed 1.4-cell RF gun can work effectively under different field gradients ranging from 30 MV/m to 100 MV/m. For a standard case of 60 MV/m, 2.5 MW peak RF power with µs level pulse width is sufficient, thus offering the feasibility for improving the repetition rate to kHz level with a standard 5 MW irradiation klystron. In addition, simulated electron beams with a low emittance of 0.29 mm.mrad@200 pC can be generated by this proposed photoinjector, showing that this high-repetition-rate injector holds the potential to deliver high-quality beams comparable to that of the state-of-the-art S-band photoinjectors. Combining merits of low emittance and high repetition rate, this proposed photoinjector will provide a new possibility for future free electron laser facilities with kHz to tens of kHz repetition rate.